Intimately connected The importance of partner responsiveness for experiencing sexual desire. [article]. - Birnbaum, G.
We investigated class-based differences in the propensity to seek positions of power. We first proposed that people?s lay theories suggest that acquiring power requires playing politics?manipulating one?s way through the social world, relying on a pragmatic and Machiavellian approach to impression management and social relationships to get ahead. Then, drawing on empirical work portraying individuals with relatively low social class as more strongly focused on others and less focused on themselves, we hypothesized that these individuals would show less interest in seeking positions of power than their high-class counterparts, because they feel less comfortable engaging in political behavior. We tested these ideas in 7 studies. Our findings indicated that, even though individuals with relatively low social class see political behavior as necessary and effective for acquiring positions of power, they are reluctant to do it; as a result, they have a weaker tendency to seek positions of power compared to individuals with relatively high social class. Consistent with our theorizing, we also found that individuals with relatively low social class intend to seek positions of power as much as their high-class counterparts when they can acquire it through prosocial means (Study 2), and when they reconstrue power as serving a superordinate goal of helping others (Study 4). Moreover, we checked the robustness of our findings by measuring social class in a number of ways within each study, and examined whether our results held across each measure. Together, our findings suggest that the common belief that political behavior is required for advancement may help explain why class inequalities persist and why creating class-based diversity in upper-level positions poses a serious challenge. -- (from the authors)
Keywords: Reis, H; Gender differences; Mate value; Responsiveness; Romantic relationships; Sexual desire